Fibroma of the Vastus Lateralis Tendon Sheath in the Thigh of the 58-year-old Female: A Rare Case Report - Heni Fatmawati; Hantonius Hantonius; Antonius Dwi Saputra; Candra Bumi (Faculty of Medicine, Universitas Jember, 2024)
Background: Fibroma of the tendon sheath (FTS) is a rare slow-growing noncancerous fibrous tumor that is usually small, painless and involves the upper extremity tendons in young adult males. FTS of the lower extremity is an unusual and underreported variety that poses a diagnostic preoperative challenge. Case description: We report an atypical case of a large fibroma of the vastus lateralis tendon in a 58-year-old female presented with a painful lump in her right thigh within the past six months. Physical examination showed a hard firm mass approximately 6 cm in diameter palpated in the anterior of the lower thigh. The mass was smooth, mobile, solid, and had well-defined borders. There was no adhesion to the skin, redness, or tenderness. MRI showed a 4,2 x 5,8 x 6,2 cm tumor with isointense signals on T1-weighted images (T1WI), heterogeneous hypointense signals on T2-weighted images (T2WI), and hyperintense signals on FatSat images. Biopsy revealed no malignant findings and the tumor had been surgically resected. Imaging studies for FTS have rarely been described, T1WI often show a low signal mass, with slight isointense to hypointense to the muscle. The T2WI’s appearance of FTS is more variable. Conclusion: In spite of rarity, FTS must still be included as a differential diagnosis of a thigh mass especially if the mass is painful and benign-appearing on physical exam and radiology.